Work Accidents and Coal Mining in Turkey - Çınar, Ibrahim; Şensöğüt, Cem (International Journal of Economic and Environmental Geology, 2022)
In this study, an up-to-date evaluation of work accidents and occupational diseases in hard coal and lignite mining in Turkey has been made using the Social Security Institution (SSI) of Turkey statistics between 2013-and 2020. For this purpose, the number of insured employees who had work accidents and occupational diseases, the number of insured people who lost their lives as a result of work accidents, and the total temporary incapacity for work (standing + inpatient) were examined. Although the number of people who had work accidents, the number of deaths after work accidents, and the total duration of temporary incapacity in the lignite mining field of activity are higher than in the field of activity in hard coal mining, it is seen that the number of occupational diseases is lower. Keywords: Coal mining, work accidents, occupational disease, occupational health, and safety.